2014
DOI: 10.3389/fnbeh.2014.00308
|View full text |Cite
|
Sign up to set email alerts
|

Early somatosensory processing in individuals at risk for developing psychoses

Abstract: Human cortical somatosensory evoked potentials (SEPs) allow an accurate investigation of thalamocortical and early cortical processing. SEPs reveal a burst of superimposed early (N20) high-frequency oscillations around 600 Hz. Previous studies reported alterations of SEPs in patients with schizophrenia. This study addresses the question whether those alterations are also observable in populations at risk for developing schizophrenia or bipolar disorders. To our knowledge to date, this is the first study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 92 publications
(121 reference statements)
2
10
0
Order By: Relevance
“…The previously reported analysis of the baseline data of the present at-risk sample showed that alterations of early sensory filtering as measured by SEPs were observable also at the at-risk level ( 15 ). Subjects at risk for psychosis showed reduced low- and high-frequency source activity compared to subjects at risk for bipolar disorders and reduced high-frequency amplitudes compared to healthy controls.…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…The previously reported analysis of the baseline data of the present at-risk sample showed that alterations of early sensory filtering as measured by SEPs were observable also at the at-risk level ( 15 ). Subjects at risk for psychosis showed reduced low- and high-frequency source activity compared to subjects at risk for bipolar disorders and reduced high-frequency amplitudes compared to healthy controls.…”
Section: Introductionsupporting
confidence: 50%
“…The aim of the present study was to explore the suitability of SEP as a neurophysiological marker. Therefore, we investigated the course of early sensory processing in help-seeking individuals being at risk to develop psychosis at the time of the baseline examination ( 15 ). Specifically, we distinguished between subjects remaining at risk at follow-up vs. subjects who converted to manifest psychosis during this time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be some evidence for modulation in clinical high-risk groups of PPI: one study has paradoxically shown that PPI is increased in cannabis use verses healthy controls but decreased in at-risk mental state subjects (Winton-Brown et al, 2015). Other studies have failed to elicit differences between P-C and P-NC in somatosensory evoked N20, P25 (Hagenmuller et al, 2014), auditory oddball N100, N200, P200 and P300 (Van Tricht et al, 2013).…”
Section: Method a Systematic Search Strategy Was Undertaken Withmentioning
confidence: 99%
“…It is of considerable interest that a recent study has reported SEP deficits in a large group of individuals who were determined to be at very high genetic risk for developing schizophrenia, 103 further suggesting that somatosensory processing deficits may prove useful as endophenotypes for this disorder. Another recent study used the steady-state response technique to assess the inter-trial temporal stability of the cortical somatosensory response in SCZ, with results pointing to both reduced amplitudes and more variable phases of the steady-state response, 104 highly reminiscent of the early work of Shagass and colleagues.…”
Section: Discussionmentioning
confidence: 99%